(untitled) (Medico Legal Update, 2020)
Arthritis is a persistent autoimmune ailment occurs more in females than in male above the age of 40. It initially affects the lining of synovial joint and the secretion of low synovial fluid also can lead to rheumatoid arthritis. It primarily affects the patient’s health swelling in joint, redness and level decreases eventually. Diagnosis at an early stage of rheumatoid arthritis is the key to prevent from severe injuries in joint and other bone related diseases. There is also several plant based anti-inflammatory compound which involves in decreasing the pathogenesis of the ailment. There are several diseases related to rheumatoid arthritis, it includes pulmonary granuloma, vesicle damages and other symptoms are expected to occur early if unnoticed. This article discusses the risk factors, damages to joint and pharmacological therapies available for the diseases.